2016
DOI: 10.1136/bmjopen-2015-010538
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and trends in non-fatal self-harm in three centres in England, 2000–2012: findings from the Multicentre Study of Self-harm in England

Abstract: ObjectivesSelf-harm is a major health problem in many countries, with potential adverse outcomes including suicide and other causes of premature death. It is important to monitor national trends in this behaviour. We examined trends in non-fatal self-harm and its management in England during the 13-year period, 2000–2012.Design and settingThis observational study was undertaken in the three centres of the Multicentre Study of Self-harm in England. Information on all episodes of self-harm by individuals aged 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(121 citation statements)
references
References 27 publications
6
111
1
3
Order By: Relevance
“…25 Recent data from the adult psychiatric morbidity survey in England, 28 based on clinical interviews, indicate that 11.7% of [16][17][18][19][20][21][22][23][24] year old females in 2007 reported ever self harming, increasing to 19.7% in 2014. In a multicentre hospital based study in England, 26 age standardised incidence of self harm appeared to decline from 2000 until 2009, with a possible increase and stabilising of rates from 2009 to 2012, although figures were based on a combined age range of 15-24 years. The trends reported in our study are consistent with the observed increase in psychological distress among adolescent girls 29 and the increase in suicide rates in England in females aged 10-29 years, of 2.7 per 100 000 in 2012 to 3.2 per 100 000 in 2015.…”
Section: Temporal Trends In Sex and Age Specific Incidencementioning
confidence: 97%
“…25 Recent data from the adult psychiatric morbidity survey in England, 28 based on clinical interviews, indicate that 11.7% of [16][17][18][19][20][21][22][23][24] year old females in 2007 reported ever self harming, increasing to 19.7% in 2014. In a multicentre hospital based study in England, 26 age standardised incidence of self harm appeared to decline from 2000 until 2009, with a possible increase and stabilising of rates from 2009 to 2012, although figures were based on a combined age range of 15-24 years. The trends reported in our study are consistent with the observed increase in psychological distress among adolescent girls 29 and the increase in suicide rates in England in females aged 10-29 years, of 2.7 per 100 000 in 2012 to 3.2 per 100 000 in 2015.…”
Section: Temporal Trends In Sex and Age Specific Incidencementioning
confidence: 97%
“…Likewise, suicide rates, which tend to follow trends in self-harm rates [2], have fallen in inner London, a change that is not explained by changes in employment or social fragmentation [16]. Such variation within urban areas remains unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…20,21,37 , il ressort de cette étude que l'intoxication est la méthode la plus cou rante associée aux hospitalisations pour blessures autoinfligées, tant chez les hom mes que chez les femmes. Par ailleurs, il a été observé que la suffocation était la principale méthode de suicide chez les deux sexes, suivie de l'intoxication chez les femmes et à la fois de l'intoxication et des armes à feu chez les hommes.…”
Section: Tendances Relatives Aux Hospitalisations Pour Blessures Autounclassified